2001
DOI: 10.1034/j.1600-0706.2001.930301.x
|View full text |Cite
|
Sign up to set email alerts
|

Context dependent effects of ectomycorrhizal species richness on tree seedling productivity

Abstract: While there has been much recent interest about the relationships between plant diversity and plant productivity, much remains unknown about how the diversity of mycorrhizal fungi affects plant productivity. We investigated the effects of ectomycorrhizal fungal community composition and diversity on the productivity and growth characteristics of seedlings of two tree species (Pinus sylvetris and Betula pendula) as well as their interactions with each other. This involved setting up a mycorrhizal fungal diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
166
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(181 citation statements)
references
References 43 publications
(54 reference statements)
11
166
2
2
Order By: Relevance
“…Furthermore, in situ ectomycorrhizal communities exhibit strong temporal differences in the capability of different EMF taxa to access litter-derived N (Pena et al, 2013a). The experimental manipulation of EMF diversity has shown context-dependent effects for fungal mixtures on plant biomass production and N nutrition (Chu-Chou and Grace, 1985;Jonsson et al, 2001). As the mechanistic concepts that explain the interactions between different EMF taxa in complex assemblages are still missing, the functional relevance of EMF identities for tree nutrition remains enigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in situ ectomycorrhizal communities exhibit strong temporal differences in the capability of different EMF taxa to access litter-derived N (Pena et al, 2013a). The experimental manipulation of EMF diversity has shown context-dependent effects for fungal mixtures on plant biomass production and N nutrition (Chu-Chou and Grace, 1985;Jonsson et al, 2001). As the mechanistic concepts that explain the interactions between different EMF taxa in complex assemblages are still missing, the functional relevance of EMF identities for tree nutrition remains enigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike us, Scagel and Linderman (1998), for Douglas fir (Pseudotsuga menziesii (Mirb.) Franco) and Lodgepole pine (Pinus contorta Douglas) seedlings at the end of the first growing season, and Jonsson et al (2001) for Scots pine (Pinus sylvestris L.) found that inoculation with mycorrhizal fungi had little effect on this ratio. Also, an increase in soil fertility is commonly associated with a reduction in the root:shoot ratio (Harris, 1992), which we confirmed with our results comparing seedlings from control treatment (1.60 ± 0.08) with other treatments applied (1.36 ± 0.07 for F treatment, 1.41 ± 0.05 for FA treatment, 0.83 ± 0.04 for FM treatment, and 0.76 ± 0.04 for FAM treatment), as Figure 2 shows.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is necessary to understand the strategy of root growth according to the soil environmental matrix for this purpose. In result of the difficulty to access root system of mature trees, studies have been usually relying in experiments with seedlings and young trees (Jonsson et al, 2001;Gogorcena et al, 2001;Rached-Kanouni et al, 2012). The seedling stage is an important and usually critical phase in the regeneration of woody species under natural conditions, since the effect of environmental stress is very high at this stage.…”
Section: Introductionmentioning
confidence: 99%
“…The re fo res ta tion process is largely determined by the intensity of the fire and the amount of area burned, and depends on the stand nature preserved after fire and the close presence of seedproducing trees (Komarova et al 2008). It is well known that mycorrhizal colonization significantly affects both the speed and the direction of any recovery processes in plant as so cia tions (Jonsson et al 2001, Smith & Read 2008, especially under conditions of prolonged and comp li cated natural regeneration of P. koraiensis forests after se vere fire (Pimenova et al 2015). Accordingly, the presence of EcM fungi is vital for the establishment of ob li ga to ry mycorrhizal framework in recurring P. koraiensis phytocoe noses, where fireresistant EcM fungi or fungi with rapid recolonization strategy from available sources of inocu lum acquire great importance.…”
Section: Discussionmentioning
confidence: 99%